2020
DOI: 10.1038/s41598-020-63366-0
|View full text |Cite
|
Sign up to set email alerts
|

Age-adjusted global glomerulosclerosis predicts renal progression more accurately in patients with IgA nephropathy

Abstract: The Oxford classification was developed to predict the outcome of IgA nephropathy (IgAN). Based on the upper reference limit (95 th percentile) for the number of globally sclerotic glomeruli (GSG) expected on biopsy according to age, we evaluated whether the prognosis of IgAN was affected by the agecalibrated numbers of GSG independent of the Oxford classification. Patients diagnosed with IgAN on renal biopsy in a single center from January 2011 to December 2018 were analyzed retrospectively. patients with mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Optimization in analysis of pathologic variables is constantly improved by testing sensitivity, specificity, and predictive values for differences in clinical features and renoprotective treatment [ 41 , 47 , 48 , 61 ]. In human pathology, lesional variables are identified and optimized in order to predict progression, outcome, and response to therapy [ 21 , 42 , 43 , 62 , 63 ]. Unfortunately, in animal studies histopathologic features only indicate the presence of lesions but not the severity because there are no commonly accepted values and each study makes assumptions based on particular set of scale values.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization in analysis of pathologic variables is constantly improved by testing sensitivity, specificity, and predictive values for differences in clinical features and renoprotective treatment [ 41 , 47 , 48 , 61 ]. In human pathology, lesional variables are identified and optimized in order to predict progression, outcome, and response to therapy [ 21 , 42 , 43 , 62 , 63 ]. Unfortunately, in animal studies histopathologic features only indicate the presence of lesions but not the severity because there are no commonly accepted values and each study makes assumptions based on particular set of scale values.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have reported the histological characteristics identified via kidney biopsy in adult patients with IgAN and the impact on disease progression. 16 , 20 , 21 , 22 , 23 Given the frequently asymptomatic presentation of IgAN and the potential negative implications of uncontrolled disease on long-term prognosis, we sought to characterize disease stage and histological patterns in a modern large real-world cohort of US adult patients with IgAN at the time of kidney biopsy. We further examined potential associations between MEST-C scores and 24-hour proteinuria as well as CKD stage at the time of diagnosis.…”
mentioning
confidence: 99%
“…However, the original Oxford study included a limited small sample size and excluded severe IgAN patients. Furthermore, recent reports indicated that GS is a strong predictor of long-term renal outcomes independent of T score in IgAN patients [8,9]. Then this retrospective three-center cohort study with a larger sample size and a longer follow-up was performed to explore the relationship between GS and renal outcomes in IgAN patients.…”
Section: Introductionmentioning
confidence: 99%